Competitive breakthrough law of CO2-CH4-N2 and gas migration pattern in coking coal - Zehua Niu; Zhaolong Ge; Liming Qiu; Changzheng Lu; Zhe Zhou (Gas Science and Engineering, 2026)

Substrate-mediated spatial cooperation in Bacillus-Saccharomyces consortia enhance starch hydrolysis and flavor formation during solid-state fermentation - Liming Wu; Yitong Ge; Zichang Peng; Zinuan Han; Jiaqi Bai; Ting Lan; Zhenchao Zhang; Fuhao Liang; Xiaole Xia (Bioresource Technology, 2026)

Climate-adaptive performance and energy-saving potential of thermochromic façade materials across China climatic zones - Chenxi Hu; Fudan Liu; Liming Ge; Zehua Zhang; Xi Meng (Building and Environment, 2026)

Zinc-reinforced sandwich-structured nano-magnesium oxide composite collagen barrier membrane for promoting bone regeneration - Hong Du; Shasha Lei; Jianhui Wu; Yiruo He; Lun Yuan; Liming Ge; Changdao Mu; Zhilang Xu; Defu Li (Chemical Engineering Journal, 2026)

Integrated multi-omics and random forest analysis reveal the role of pea-derived nitrogen in shaping microbial-enzymatic networks and amino acid metabolism in medium-high-temperature Daqu - Liming Wu; Shuaijun Wang; Shicong Liang; Yitong Ge; Fuhao Liang; Xiaole Xia (Food Bioscience, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Temperature-mediated shift from competitive to facilitative interactions between lactic acid bacteria and bacillus species in daqu fermentation: Insights from metagenomics, dual RNA-seq, and coculture analysis - Liming Wu; Meiyu Yan; Xinlei Huang; Hui Liao; Daixiu Bao; Yitong Ge; Shuaijun Wang; Xiaole Xia (International Journal of Food Microbiology, 2025)

Microbial metabolisms determine soil priming effect induced by organic inputs - Yingyi Fu; Wanling Liu; Zhiyi Chen; Marc Redmile-Gordon; Chao Liang; Caixian Tang; Georg Guggenberger; Shaobin Yan; Liming Yin; Jingjing Peng; Lukas Van Zwieten; Peng Wang; et al. (Soil Biology and Biochemistry, 2025)

Field-based phenotyping for poplar seedlings biomass evaluation based on zero-shot segmentation with multimodal UAV images - Qifei Tian; Huichun Zhang; Liming Bian; Lei Zhou; Zhuhao Shen; Yufeng Ge (Computers and Electronics in Agriculture, 2025)

Soil quality evaluation of typical ecological restoration slopes - Liming Liu; Qian Peng; Hongwei Tian; Mingwei Li; Mingtao Zhou; Jiale Ge; Bin Wu; Mingyi Li; Dong Xia (Journal of Mountain Science, 2025)

Correction: Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)

Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex ( E. rex ) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14 C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.

Hyperspectral image classification based on faster residual multi-branch spiking neural network - Yahui Li; Yang Liu; Rui Li; Liming Zhou; Lanxue Dang; Huiyu Mu; Qiang Ge (Computers & Geosciences, 2025)

Employing the spray system to improve the regional thermal environment in outdoor open space - Yi Gao; Liming Ge; Xi Meng (Urban Climate, 2025)

Vegetation and environmental changes on the Northeast China Plain during warm periods since MIS 3 - Liming Xu; Zhipeng Li; Pai Yue; Weijie Tang; Yiren Liu; Wei Chen; Min Xu; Jinglian Ge (Review of Palaeobotany and Palynology, 2024)

Evaluating drought stress response of poplar seedlings using a proximal sensing platform via multi-parameter phenotyping and two-stage machine learning - Xuexing Fan; Huichun Zhang; Lei Zhou; Liming Bian; Xiuliang Jin; Luozhong Tang; Yufeng Ge (Computers and Electronics in Agriculture, 2024)

Optimizing herbicide types and concentrations: Crucial elements for achieving intensive cultivation of common buckwheat - Qi Wang; Xiaona Wang; Liming Yang; Youxiu Chen; Jiahao Ge; Jincai Tao; Chenxi Wan; Pu Yang; Pengke Wang; Jinfeng Gao (Crop Protection, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Regulation of fadR on the ROS defense mechanism in Shewanalla oneidensis - Qiu Meng; Yinming Xu; Liming Dai; Xuzhe Ge; Pei Qiao (Biotechnology Letters, 2024)

The novel probiotic preparation based on Lactobacillus spp. mixture on the intestinal bacterial community structure of Cherry Valley duck - Shuiqin Shi; Mengrui Ge; Yan Xiong; Yixun Zhang; Wenhui Li; Zhimuzi Liu; Jianfen Wang; Enhui He; Liming Wang; Duoqi Zhou (World Journal of Microbiology and Biotechnology, 2024)

CDC-like kinase 3 deficiency aggravates hypoxia-induced cardiomyocyte apoptosis through AKT signaling pathway - Xiue Ma; Liming Gao; Rucun Ge; Tianyou Yuan; Bowen Lin; Lixiao Zhen (In Vitro Cellular & Developmental Biology - Animal, 2024)

The Influence of Seamounts on the Enrichment of Rare Earth Elements in Sediments—A Case Study of the Marcus-Wake Seamounts in the Western Pacific Ocean - Tinglu Xiao; Dong Xu; Tao Deng; Junyu Lin; Liming Ye; Qian Ge; Xibin Han; Yanhui Dong; Fengyou Chu (Journal of Marine Science and Engineering, 2024)
Deep-sea sediments enriched in rare earth elements and yttrium (REY-rich sediments) are widely distributed on the deep-sea floor, and their formation mechanism remains elusive. Although studies have recognized the link between seamounts and REY-rich sediments, in-depth analysis of the specific roles and effects of seamounts in the formation of REY-rich sediments is lacking. In this study, we analyzed surface sediments from the Marcus-Wake Seamounts for grain size, geochemistry, and mineral composition and classified the samples into three types: samples with moderate REY content and dominated by terrestrial detritus; samples with high REY and authigenic mineral content; and samples rich in CaCO3 but poor in REY. The REY in the sediments of the study area partly originate from Asian dust input and partly from seawater and/or pore water, and are mainly enriched in REY carrier particles including bioapatite fossils and micronodules. The amount of REY carrier particles influences the REY content in the sediments. The current field, primary productivity, weathering process, and depositional environment around seamounts are different from those of abyssal plains, which are conducive to the formation of REY-rich sediments. Strong bottom currents may exist in the southeastern direction of some large seamounts (e.g., Niulang Guyot), leading to the selective accumulation of REY-rich bioapatite fossils and micronodules, resulting in the formation of REY-rich sediments.

Effect of water mist stimulation on dynamic thermal response of pedestrians in summer - Yi Gao; Liming Ge; Tian Zhong; Xi Meng (Building and Environment, 2023)

Design and analysis of wire-driven tail fin for bionic underwater glider - Liming Ge; Wenda Ma; Shaoqiong Yang; Xiao Yu; Tongshuai Sun; Xuan Wang; Shuai Fa; Yanhui Wang (Ocean Engineering, 2023)

Boosted water electrolysis capability of NixCoyP via charge redistribution and surface activation - Haobo Liu; Jiancheng Li; Yuqi Zhang; Riyue Ge; Jack Yang; Ying Li; Jiujun Zhang; Mingyuan Zhu; Sean Li; Bin Liu; Liming Dai; Wenxian Li (Chemical Engineering Journal, 2023)

Enhancing wuyiencin productivity of Streptomyces albulus (CK15) by mutagenesis breeding with atmospheric and room temperature plasma - Yu Wah Thein; Liming Shi; Binghua Liu; Qiuhe Wei; Kecheng Zhang; Beibei Ge (World Journal of Microbiology and Biotechnology, 2023)

How do intellectual property demonstration cities contribute to low-carbon development? Evidence from China - Wei Jiang; Nana Jiang; Liming Ge (Environmental Science and Pollution Research, 2023)

Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing - Weiwei Tan; Tao Long; Yanzhuo Wan; Bingchen Li; Zhilang Xu; Lei Zhao; Changdao Mu; Liming Ge; Defu Li (Carbohydrate Polymers, 2023)

An insight into direct water injection applied on the hydrogen-enriched rotary engine - Cheng Shi; Sen Chai; Huaiyu Wang; Changwei Ji; Yunshan Ge; Liming Di (Fuel, 2023)

Sources and spatial variations of heavy metals in offshore sediments of the western Pearl River Estuary - Jianru Zhao; Kehong Yang; Fengyou Chu; Qian Ge; Dong Xu; Xibin Han; Liming Ye (Marine Pollution Bulletin, 2023)

Policy shock effect of SDP on environmental total factors productivity: 53 coal cities versus 165 non-resource-based cities - Huihui Chen; Zhenling Chen; Heyun Zheng; Liming Ge; Xiaofang Gao (Environmental Science and Pollution Research, 2022)

Effect of toyF on wuyiencin and toyocamycin production by Streptomyces albulus CK-15 - Binghua Liu; Qiuhe Wei; Miaoling Yang; Liming Shi; Kecheng Zhang; Beibei Ge (World Journal of Microbiology and Biotechnology, 2022)

Impacts of the efficiencies of identification and tracking algorithms on the statistical properties of global mesoscale eddies using merged altimeter data - Fenglin Tian; Di Wu; Liming Yuan; Ge Chen (International Journal of Remote Sensing, 2020)

Linking Monsoon Activity with River-Derived Sediments Deposition in the Northern South China Sea - Qian Ge; Dong Xu; Liming Ye; Kehong Yang; Zhigang Yao (Journal of Ocean University of China, 2019)

Distribution Patterns of Major and Trace Elements and Provenance of Surface Sediments on the Continental Shelf off Western Guangdong Province and Northeastern Hainan Island - Qian Ge; Z. George Xue; Liming Ye; Dong Xu; Zhigang Yao; Fengyou Chu (Journal of Ocean University of China, 2019)

The spatial distribution of major and trace elements of surface sediments in the northeastern Beibu Gulf of the South China Sea - Qian Ge; George Z. Xue; Liming Ye; Dong Xu; Jianru Zhao; Fengyou Chu (Acta Oceanologica Sinica, 2019)

Comprehensive analysis of tropomyosin isoforms in skeletal muscles by top-down proteomics - Yutong Jin; Ying Peng; Ziqing Lin; Yi-Chen Chen; Liming Wei; Timothy A. Hacker; Lars Larsson; Ying Ge (Journal of Muscle Research and Cell Motility, 2016)

Influences of introducing frogs in the paddy fields on soil properties and rice growth - Qing Teng; Xue-Feng Hu; Fan Luo; Chang Cheng; Xinyi Ge; Minyong Yang; Liming Liu (Journal of Soils and Sediments, 2016)